Pengukuran Kualitas Website Labotatorium Komputer Stikom Surabaya Menggunakan Metode Webqual 4.0 - Filzah Apritasari; Henry Bambang Setyawan; Tegar Heru Susilo (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Computer Laboratory (Labkom) with labkom.stikom.edu domain is a facility supporting academic activities. Activities supported is practice to lecture both practice or not. Currently, Labkom not only used for the purposes of practical subjects but also used  for other activities such as research, computer training, community service, and performing tasks students. Website Labkom  first used in  August 2011. During this Labkom website has never done an assessment of the quality of the website is based on the perception of site visitors. In this research, measured by the quality of the website Labkom by using  WebQual method 4.0. WebQual is an instrument that assesses the quality of a website according to the end-user perspective. This research was conducted using questionnaire, from the spread of the questionnaire obtained 83 respondents. Data obtained from the questionnaire in trials using validity, reliability test, and test the assumptions. Then processed by multiple linear regression. From  the results of this study concluded  that WebQual variable is the interaction  quality is positive and significant impact on user satisfaction Labkom website, but the need for evaluation and improvement based on indicators of WebQual.